Improved diagnostic performance of high-sensitivity cardiac troponins in muscle dystrophies using comprehensive definition criteria for cardiac involvement: a longitudinal study on 35 patients - Yildirim, Mustafa; Salbach, Christian; Reich, Christoph; Pribe-Wolferts, Regina; Milles, Barbara Ruth; Täger, Tobias; Müller-Hennessen, Matthias; Weiler, Markus; Meder, Benjamin; Frey, Norbert; Giannitsis, Evangelos (European journal of neurology, 2024)
Background and purpose Sparse information is available on the correct interpretation of elevated high-sensitivity cardiac troponin (hs-cTn) in confirmed muscular dystrophies. Methods Serum concentrations of hs-cTn T (hs-cTnT) and hs-cTn I (hs-cTnI) were determined in 35 stable outpatients with confirmed skeletal muscle dystrophies. We calculated sensitivities, specificities, and positive and negative predictive values of hs-cTnT and hs-cTnI for identification of cardiac involvement using a comprehensive definition that included diastolic left ventricular and right ventricular function, strain analysis using two-dimensional transthoracic echocardiogram and magnetic resonance imaging, myocardial biopsies, and consideration of a variety of triggers for cardiac injury, including arrhythmias, conduction disorders, and hypoxemia due to respiratory failure. Results Cardiac involvement was diagnosed in 34 of 35 cases. Specificities of hs-cTnT increased from 12.5% to 100% (p = 0.0006) applying the comprehensive definition compared to a definition based on electrocardiography and echocardiography alone. At the recommended 99th percentile upper limit of normal, sensitivities were significantly lower for hs-cTnI than for hs-cTnT (29.4% vs. 100%, p = 0.0164). Conversely, the specificities of hs-cTnT and hs-cTnI increased to 100% when using the comprehensive definition criteria for diagnosing cardiac involvement. Conclusions Elevated hs-cTnT but not hs-cTnI discriminates cardiac involvement in cases with confirmed skeletal muscle dystrophies with very high sensitivity and 100% specificity. Prior reports on worse performance may be explained by the use of less sensitive imaging methods or incomplete assessment of cardiac involvement.
Online veröffentlicht: 30. September 2024
Gesehen am 19.03.2025